Evaluation of systemic insecticides mixed in rodenticide baits for plague vector control - Larsen, Kim Søholt; Lodal, Jens (1997)
Rodenticide baits containing systemic insecticides were evaluated in the laboratory for their palatability to the house rat Rattus rattus and for their toxicity against the oriental rat flea Xenopsylla cheopis - both animals are important Vectors of plague in Africa. The test bait and a non-poisonous alternative were given to the rats for four days. The evaluation of the effectiveness was based on mortality and poison bait intake in percent of the total consumption. Different concentrations of technical material and different types of encapsulation of the three insecticides phoxim, fenthion and dimethoate were used in the tests. The rodenticide used was 0.005 % bromadiolone. For all three insecticides, a reduced intake of the poisonous bait was observed compared with the test of bromadiolone without insecticide. Based on the acceptance of the baits, the dimethoate encapsulated with beef tallow only was considered as the most promising candidate. The formulation was tested on flea infested rats and after four days, a raised flea mortality was observed.